ANALISIS PENERAPAN STANDAR AKUNTANSI PEMERINTAH DALAM PENYUSUNAN LAPORAN KEUANGAN DI BADAN PENDAPATAN DAERAH (BAPENDA) KABUPATEN KOLAKA - Pandin, Enjois Rongre; Triani, Neks; Ilham, Surianto (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the implementation of Government Accounting Standards (SAP) in the preparation of financial statements at the Regional Revenue Agency of Kolaka Regency. SAP serves as an important guideline in realizing transparency and accountability in regional financial management. This study was conducted using a qualitative method. The data sources used in this research include primary and secondary data. In collecting data, the researcher employed observation, interviews, and documentation techniques. The research was carried out at the office of the Regional Revenue Agency of Kolaka Regency. The analysis results indicate that, in general, the Regional Revenue Agency of Kolaka Regency has implemented accrual-based SAP in accordance with Government Regulation Number 71 of 2010. However, there are still several obstacles affecting the effectiveness of its implementation, including limitations in human resources (HR) with competencies in public sector accounting, suboptimal financial information systems, and the need for technical adjustments in understanding reporting formats and procedures. Additionally, coordination between accounting entities and main reporting entities needs to be strengthened to produce financial statements that are more accurate, relevant, and timely. Based on these findings, this study recommends enhancing HR capacity through specialized training, strengthening information systems, continuous internal evaluation and supervision, as well as improving cross-unit coordination so that the implementation of SAP can run more optimally and support the achievement of good governance within the Kolaka Regency Government environment